Interoceptive Insular Cortex Mediates Both Innate Fear and Contextual Threat Conditioning to Predator Odor - Rodríguez, María; Ceric, Francisco; Murgas, Paola; Harland, Bruce; Torrealba, Fernando; Contreras, Marco (Frontiers in Behavioral Neuroscience, 2020)
The insular cortex (IC), among other brain regions, becomes active when humans experience fear or anxiety. However, few experimental studies in rats have implicated the IC in threat responses. We have recently reported that inactivation of the primary interoceptive cortex (pIC) during pre-training, or the intra-pIC blockade of protein synthesis immediately after training, impaired the consolidation of auditory fear conditioning. The present study was designed to investigate the role of the pIC in innate and learned defensive responses to predator odor. Freezing behavior was elicited by single or repetitive exposures to a collar that had been worn by a domestic cat. Sessions were video-recorded and later scored by video observation. We found that muscimol inactivation of the pIC reduced the expression of freezing reaction in response to a single or repeated exposure to cat odor. We also found that pIC inactivation with muscimol impaired conditioning of fear to the context in which rats were exposed to cat odor. Furthermore, neosaxitoxin inactivation of the pIC resulted in a prolonged and robust reduction in freezing response in subsequent re-exposures to cat odor. In addition, freezing behavior significantly correlated with the neural activity of the IC. The present results suggest that the IC is involved in the expression of both innate and learned fear responses to predator odor.